2016
DOI: 10.1021/acs.chemmater.6b02069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Substituents on the Electronic Structure and Degradation Process in Carbazole Derivatives for Blue OLED Host Materials

Abstract: We investigate the dissociation mechanism of the C−N bond between carbazole and dibenzothiophene in carbazole-dibenzothiophene (Cz-DBT) positional isomers, selected as representative systems for blue host materials in organic lightemitting diodes (OLEDs). The C−N bond dissociation energies, calculated at the density functional theory level, are found to depend strongly on the charge states of the parental molecules. In particular, the anionic C−N bond dissociations resulting in a carbazole anion can have low d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 55 publications
2
60
0
Order By: Relevance
“…This observation was also reported recently by Hong et al [21] The BDE À of the CN s-bond in the ET À -HT 0 anion is small largely because the N-sp 2 (HT) level of HT lies much lower than the p* LU(ET) level of ET. This observation was also reported recently by Hong et al [21] The BDE À of the CN s-bond in the ET À -HT 0 anion is small largely because the N-sp 2 (HT) level of HT lies much lower than the p* LU(ET) level of ET.…”
Section: Enhancing the Kinetic Stability And Lifetime Of Organic Lighsupporting
confidence: 86%
“…This observation was also reported recently by Hong et al [21] The BDE À of the CN s-bond in the ET À -HT 0 anion is small largely because the N-sp 2 (HT) level of HT lies much lower than the p* LU(ET) level of ET. This observation was also reported recently by Hong et al [21] The BDE À of the CN s-bond in the ET À -HT 0 anion is small largely because the N-sp 2 (HT) level of HT lies much lower than the p* LU(ET) level of ET.…”
Section: Enhancing the Kinetic Stability And Lifetime Of Organic Lighsupporting
confidence: 86%
“…Continuous oxidation and reduction processes happening inside the device by carrier injection generate positive and negative polarons, which cause electrochemical degradation. Many works have shown that organic materials become unstable under positive or negative polarons even though they are stable without any polarons …”
Section: Basic Mechanism Of Degradationmentioning
confidence: 99%
“…[ 1,10,11 ] Generally, the C–N bond between donor and acceptor moieties is weaker than the C–C bond and simultaneously causes the low bond dissociation energy (BDE). [ 12,13 ] On the other hand, blue TADF emitters have high T 1 , resulting in the utilization of phosphine oxide‐based host materials such as bis[2‐(diphenylphosphino)phenyl] ether oxide (DPEPO) and dibenzo[b,d]furan‐2,8‐diylbis(diphenylphosphine oxide) (DBFPO) due to their high T 1 values. [ 14,15 ] However, such phosphine oxide‐based host materials show low operational stability because of their very low BDE.…”
Section: Introductionmentioning
confidence: 99%